Phenotypic Description of the Spanish Multicentre Genetic Glaucoma Group Cohort - Elena Milla; Maria José Gamundi; Susana Duch; Jose Rios; Miguel Carballo; EMEIGG Study Group (Journal of Ophthalmology)
Introduction. The aim of the study was to make a phenotypic description of the Spanish multicentre glaucoma group cohort of patients. Design. Retrospective, observational, multicentre, cohort study. Material and Methods. The clinical charts of 152 patients with hereditary glaucoma from18 Spanish eye centres were reviewed in order to make an epidemiologic description of the type of glaucoma and associated factors. True hereditary cases were compared with familiar cases according to the Gong et al. criteria. Results. 61% were true hereditary cases and 39% familiar cases. Ocular comorbidity, optic disc damage, and visual field mean defect were significantly more severe in hereditary patients, who required significantly more first-line hypotensive drugs and surgical interventions to control intraocular pressure than familiar patients. Conclusions. The strength of the hereditary component of glaucoma seems to worsen the clinical course, causing more structural and functional damage and requiring more intense glaucoma treatment. The family history of glaucoma should be carefully investigated and taken into consideration when making treatment decisions or intensifying previous treatment.